Flipped classroom approach for enhancing linguistic competence - Rivera, Maricel Demoral; Flores, Grace Manatad (International Journal of Evaluation and Research in Education (IJERE), 2024)
Nowadays, technology has become an indispensable instructional tool. Technology-integrated teaching approach has been recognized in research studies as an effective means to address the declination of the English language’s linguistic competence of the learners. This research determined the effectiveness of a flipped classroom, a technology-integrated teaching approach, to a specific group of Filipino language learners. Utilizing a quasi-experimental research design, 102 English pre-service teachers enrolled in a state university were selected purposively to be the participants of the study and were categorized into two groups, the very good, and the good groups. The expert-validated pre-post-test questionnaire, course syllabus, and lesson exemplars were used to gather the data on learners’ linguistic competence. Results of the paired t-test revealed a significant mean gain of the students’ scores both from very good and good groups pre-post the employment of the flipped classroom approach. The flipped classroom approach is one of the technology-integrated approaches to be used to augment the learners’ linguistic competence regardless of students’ group categories. It is recommended that the flipped classroom approach be used by teachers handling different disciplines delivered in English to mitigate the students’ dilemma on English language proficiency.